The crosstalk effect between ferrous and other ions metabolism in ferroptosis for therapy of cancer - Ke, Kun; Li, Li; Lu, Chao; Zhu, Qicong; Wang, Yuanyu; Mou, Yiping; Wang, Huiju; Jin, Weiwei (Frontiers in Oncology, 2022)
Ferroptosis is an iron-dependent cell death process characterized by excessive accumulation of reactive oxygen species and lipid peroxidation. The elucidation of ferroptosis pathways may lead to novel cancer therapies. Current evidence suggests that the mechanism of ferroptosis can be summarized as oxidative stress and antioxidant defense mechanisms. During this process, ferrous ions play a crucial role in cellular oxidation, plasma membrane damage, reactive oxygen species removal imbalance and lipid peroxidation. Although, disregulation of intracellular cations (Fe2+, Ca2+, Zn2+, etc.) and anions (Cl-, etc.) have been widely reported to be involved in ferroptosis, their specific regulatory mechanisms have not been established. To further understand the crosstalk effect between ferrous and other ions in ferroptosis, we reviewed the ferroptosis process from the perspective of ions metabolism. In addition, the role of ferrous and other ions in tumor therapy is briefly summarized.